The Role of Communication Skills on Perspectives of University Students about Marriage during Dating (Emotional Friendship) - Dincyurek, Sibel; Uygarer, Gulen (Ani Yayincilik, 2012)
Problem Statement: Marriage is considerable attempt for everyone. During decision taking, people are affected by something for this reason some things cause problems or good things for marriage. In the study, relationship is observed to specific variables and marriage. Relationships are; there is a relationship between communication skills and preferring marital mate. Also, there is a relationship between particular differences (age, gender, nationality, attitudes of mother and father) and preferring martial mate. Purpose of the Study: The aim of the study is to indicate role of communication skills on aspects of university students about marriage during dating. In every phase of life, family and marriage have vital position for human beings. Therefore, the study had been conducted to show importance of the communication skills among partners during marriage. Methods: Mix research methodology was preferred for the study as a research methodology. Case study was determined as a research design. Population of the study was EMU's undergraduate students. Participants of the study were chosen from EMU. 300 undergraduate was chosen by strafed sampling method for quantitative part of the study and 30 participants were chosen for qualitative part of the study. One scale and semi-structure interview question were used to gather data. SPSS was used to analyze gathered data. Nationality, gender, and age, attitudes of mother and father are important variable to analyze collected data. Results: The results of the study reflect that communication skills have importance on university students' aspects about marriage during date. Attitudes of mother have impact on decisions about marital mate. Discussion and Conclusions: Communication is vital part of the human beings' life and influences every phase of human beings' life. Therefore, during dating and getting married, function of communication skills can be observable and people should show more interests to this field to emphasize the importance of communication for marriage.
Keywords: Communication skills; marriage; dating; university students